The Deification of English - Nikalje, Varada M. (THE PRIMARY TEACHER, 2015)
I remember a news item published a few years ago which stated that a temple was being built in honour of the “Goddess of English”, in a small village called Banka in Lakhimpur Kheri district in Uttar Pradesh. The foundation stone was laid on April 30, 2010, in a simple ceremony, with women singing ‘Jai Angrezi Devi Maiyaa Ki’, (Long live Mother Goddess of English) in honour of the goddess. Donations were already pouring in for a temple. Intrigued, I took in the details. The temple was to be a single-story structure covered with black granite. It was being built on the premises of a local school, the Dalit-run Nalanda Public Shiksha Niketan. The temple would be run by a trust. A 30 inch brass image of the goddess was brought from New Delhi to the village for the consecration, which was attended by around 1,000 villagers. (The news item stated that 3 feet high statue of the goddess would be installed at a later stage).